“There Is No Good War”: The Firebombing of Dresden and Kurt Vonnegut’s View Towards World War II in Slaughterhouse-Five - Ilhamdi Hafiz Sofyan (Vivid: Journal of Language and Literature, 2017)
This study discusses Kurt Vonnegut's view of war reflected in his novel Slaughterhouse-Five and also his efforts in conveying his views through his novel. This novel is based on the experience of Kurt Vonnegut during World War II when he was imprisoned in a German city called Dresden and witnessed the destruction of the city on February 13, 1945 in an Allied bombing operation. In the novel, Vonnegut rewrote his experience in the form of a fiction. In discussing this literary work, I used the expressive theory by M. H. Abrams which was supported by a historical and biographical approach. In analyzing this literary work, I took quotes from the novel Slaughterhouse-Five as the main data as well as other data as secondary data, such as the biography of the author, interviews with the author taken from various sources, as well as writings on author that is relevant to the discussion in this study. The result show that  Kurt Vonnegut see war as something that was completely meaningless and only caused destruction and death for innocent residents. Kurt Vonnegut uses narrative techniques such as black humor, irony, and metaphysics at Slaughterhouse-Five so that his views on war can be conveyed to his readers.